Batman : Nightwalker - Lu, Marie, 1984- (DC Icons, 2018)
"The Nightwalkers are terrorizing Gotham City, and Bruce Wayne is next on their list.... Bruce will walk the dark line between trust and betrayal as the Nightwalkers circle closer"--